PENGARUH CELEBRITY ENDORSEMENTTERHADAP PURCHASE INTENTION DENGANBRAND IMAGE SEBAGAI VARIABEL INTERVENING (STUDI KASUS IKLAN PRODUK PERAWATAN KECANTIKAN POND’S) - Finna Anastasia Wijaya; Sugiono Sugiharto (Jurnal Manajemen Pemasaran, 2015)
This study aims to analyze the influence of Credibility , Attractiveness , and Power to Purchase Intention beauty products Pond'sdengan consider factors Brand Image ( Sincerity , Excitement , Competence , and Shophistication ) .Penelitian conducted by distributing questionnaires to 100 respondents who had seen the ads Pond's in the last 2 months . Analysis technique used is the technique of quantitative analysis analysis.Hasil path method showed that the variables that have a significant effect only Attractiveness, Power , Brand image and Purchase intention